Response surface optimization and modeling of caffeine photocatalytic degradation using visible light responsive perovskite structured LaMnO3 - Ibrahim, Muktar Musa; Sani, Hamza Rabiu; Yahuza, Khuzaifa Muhammad; Yusuf, Aminu Hassan; Bungudu, Ahmad Bello (European Journal of Chemistry, 2021)
Caffeine is a refractory pollutant of emerging concern that evades conventional waste-water treatment techniques. Here, we report the synthesis of visible light responsive perovskite structured LaMnO3 photocatalyst using modified Pechini method and utilized it as an efficient photocatalyst for caffeine degradation. XRD, BET, UV-Vis, NH3-TPD, and SEM were used to characterize the photocatalyst. Response surface methodology using Central composite design was used to investigate the effect of three operational variables; catalyst dosage, initial caffeine concentration and pH on the caffeine photocatalytic degradation efficiency. The functional relationship between these operational variables and caffeine photocatalytic degradation efficiency was established be a second order polynomial model. The results of the response surface analysis indicate caffeine degradation efficiency is most significantly affected by catalyst dosage and pH. The optimal values of operational obtained by response surface optimization were found be 3.5 g/L for catalyst dosage, 7.9 and 44.6 mg/L for pH and initial caffeine concentration respectively given the caffeine degradation efficiency of 93.9%.